Probing the biophysical interplay between a viral genome and its capsid - Snijder, J. (2013)
The interaction between a viral capsid and its genome governs crucial steps in the life cycle of a virus, such as assembly and genome uncoating. Tuning cargo–capsid interactions is also essential for successful design and cargo delivery in engineered viral systems. Here we investigate the interplay between cargo and capsid for the picorna-like Triatoma virus using a combined native mass spectrometry and atomic force microscopy approach. We propose a topology and assembly model in which heterotrimeric pentons that consist of five copies of structural proteins VP1, VP2 and VP3 are the free principal units of assembly. The interpenton contacts are established primarily by VP2. The dual role of the genome is first to stabilize the densely packed virion and, on an increase in pH, second to trigger uncoating by relaxing the stabilizing interactions with the capsid. Uncoating occurs through a labile intermediate state of the virion that reversibly disassembles into pentons with the concomitant release of protein VP4.